Comparative characteristics of thematic variation in English and Russian language medical conflict communication - Kudoyarova, O.V. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2011)
The article focuses on revealing the potential of themes and topics realized by English and Russian speaking medicians in professional conflict situations. The establishing of thematic potential qualitative characteristics lies in revealing the realized themes and topics, followed by their frequency value analysis. The comparison of qualitative and quantitative parameters forms the basis for establishing the universal and cultural-specific features of medical professional conflict discourse thematic aspect.
Keywords: English language; medical professional conflict discourse; qualitative characteristics; quantitative parameters; Russian language; thematic potential; theme; topic